2017
DOI: 10.1016/j.bbamem.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

PGLa-H tandem-repeat peptides active against multidrug resistant clinical bacterial isolates

Abstract: Antimicrobial peptides (AMPs) are promising candidates for new antibiotic classes but often display an unacceptably high toxicity towards human cells. A naturally produced C-terminal fragment of PGLa, named PGLa-H, has been reported to have a very low haemolytic activity while maintaining a moderate antibacterial activity. A sequential tandem repeat of this fragment, diPGLa-H, was designed, as well as an analogue with a Val to Gly substitution at a key position. These peptides showed markedly improved in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 63 publications
6
24
0
Order By: Relevance
“…The presence of SDS micelles induced a transition from random coil to helical structures as indicated by the two minima at 222 nm and 209 nm and a maximum at 192 nm. The experiments performed at 298 K showed slightly higher intensities than at 323 K, especially for Kiadin, but overall the CD experiments did not show any significant difference in secondary structure content between both peptides, as previously reported 7 . Glycine is often reported as a helix-breaking residue due to its large conformational space of phi-psi angles and thus increased entropy of the backbone in the coil structure 9 .…”
Section: Kiadin and Dipgla-h Produced Similar CD Lineshapesupporting
confidence: 86%
“…The presence of SDS micelles induced a transition from random coil to helical structures as indicated by the two minima at 222 nm and 209 nm and a maximum at 192 nm. The experiments performed at 298 K showed slightly higher intensities than at 323 K, especially for Kiadin, but overall the CD experiments did not show any significant difference in secondary structure content between both peptides, as previously reported 7 . Glycine is often reported as a helix-breaking residue due to its large conformational space of phi-psi angles and thus increased entropy of the backbone in the coil structure 9 .…”
Section: Kiadin and Dipgla-h Produced Similar CD Lineshapesupporting
confidence: 86%
“…A previous study has indicated that the antibacterial activities of fowlicidin-2 and tritrpticin were inhibited by the addition of salts and porcine serum [33]. In the present study, the hybrid peptides CA-FO and CA-TP were designed by combining CA (1)(2)(3)(4)(5)(6)(7)(8) with the most potent region of Fowlicidin-2 (1-15) [33] or the antimicrobial center of tritrpticin (7)(8)(9)(10)(11)(12)(13) [34,35]. We indicated the success of hybridization in designing AMPs with increased salt resistance and cell selectivity.…”
Section: Introductionmentioning
confidence: 90%
“…2 Purity was determined by reverse-phase high performance liquid chromatography (RP-HPLC). 3 Grand average of hydropathicity (GRAVY). Higher positive score indicates greater hydrophobicity and vice versa.…”
Section: Physicochemical Parameters Of Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Maravic and co-workers studied the effect of conformational flexibility in antimicrobial activity upon modification of a natural poorly active antimicrobial peptides PGLaÀ H. [25] They designed and synthesized a bunch of small cationic (charges varies from + 4 to + 7) peptides and conducted the antibacterial activity studies of the same with various Gram-positive and Gramnegative bacterial pathogens including the ESCAPE pathogens such as E. coli, K. pneumoniae, P. aeruginosa, A. baumannii and S. aureus. [26] Among the various number of Gly residue rich peptides (named as Kiadin), Kiadin-2 (KIAKGALKALKIAKVALKAL-NH 2 ) was found to be the most potent against Gram-negative pathogens.…”
Section: Conformational Effect On Natural Ampsmentioning
confidence: 99%